PENGUATAN PENDIDIKAN KARAKTER PESERTA DIDIK MELALUI PROGRAM PENDIDIKAN BERNUANSA SURAU DAN BUDAYA MINANGKABAU - Afridinata, Heri; Samad, Duski; Kosim, Muhammad (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This study aims to describe and analyze the application of the character education program based surau and the Minangkabau culture strengthening program in intracurricular, extracurricular activities; and through school culture. This study used a qualitative approach and interviews, observation and documentation use to collect the data. Some teachers are respondents of the research. The results showed that the implementation of the Minangkabau culture and character education program in intracuricular activities were carried out by the subject teacher by incorporating the values of the Minangkabau nuanced character and culture into each learning. Character values were embedded in learning tools such as prayer and reading the Al- Qur’an before and after learning activities. Whereas the implementation of the character education program and the Minangkabau culture in extracurricular activities was carried out through the integration of the values of the character and the Minangkabau culture in various extra-curricular activities such as muhadarah, An Nisa forum, Ar Rijal forum (studying Islamic sciences with the halaqah method), pesantren , and pray. While strengthening the values of Minangkabau cultural character can be seen in randai activities, traditional speeches, and Minangkabau cuisine. The results also showed that the development of school culture was carried out through strengthening the character of students such as Adiwiyata School, Healthy and Smoke-Free School Program. It is concluded that character education based surau and Minangkabau culture had helped educators more easily to develop students' character. The implication is that educators need to develop teaching materials that can help students improve their character.